Eksplorasi Pemberian Kartu Masalah untuk Meningkatkan Kemampuan Numerasi Siswa Kelas VII SMP Negeri 1 Pakis - Syaiful Hamzah Nasution; Zulian Putri Rahmawati; Aizzatul Masruroh; Achriani Galuh Anjarini (Jurnal Tadris Matematika, 2022)
The results of the 2018 PISA test show that Indonesian students' math ability scores are ranked 7th from the bottom. This shows that the numeracy skills of Indonesian students are low. Based on an interview with one of the teachers at SMP Negeri 1 Pakis, information was obtained that the numeracy skills of students at SMP Negeri 1 Pakis were low. This is due to students' lack of numeracy questions, and teachers often give routine questions requiring procedural skills. This is a classroom action research that explores the teacher's actions to improve the numeracy skills of seventh-grade students of SMP Negeri 1 Pakis Malang by giving problem cards. The research subjects were 32 Class VII D students of SMP Negeri 1 Pakis Malang in the academic year 2021/2022. The research instruments include lesson plans, problem cards, test questions, observation sheets, interview guidelines, and field notes. Data analysis techniques include data reduction, presenting data, and drawing conclusions and verification. The results showed an increase in students with a KKM score of 30.77% and Classical Learning Completeness of 26.26%. The study shows that giving problem cards can improve students' numeracy skills. Through the Problem Card, students are allowed to write down the information asked in their language and are given guidance/instructions to solve the given problem.